The Potential of Natural Compounds Regulating Autophagy in the Treatment of Osteoporosis - Zhao Y; Qu Z; Zhao S; Zhang Y; Gong Y; Zhang B; Gao X; Wang D; Yan L (Journal of Inflammation Research, 2023)
Yiwei Zhao,* Zechao Qu,* Songchuan Zhao, Yong Zhang, Yining Gong, Bo Zhang, Xiangcheng Gao, Dong Wang, Liang Yan Department of Spine Surgery, Honghui Hospital, Xi’an Jiao Tong University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liang Yan, Department of Spine Surgery, Honghui Hospital, Xi’an Jiao Tong University, Xi’an, People’s Republic of China, Email yanliangdr5583@163.comAbstract: The maintenance of bone homeostasis is dynamically regulated by osteoblast-mediated bone formation and osteoclast-mediated bone resorption. Abnormal differentiation of osteoclast and insufficient osteoblast production can cause bone diseases such as osteoporosis. As one of the highly conserved catabolic pathways in eukaryotic cells, autophagy plays an important role in maintaining cell homeostasis, stress injury repair, proliferation and differentiation. Numerous studies have found that autophagy activity is essential for the survival, differentiation and function of bone cells, and that regulation of autophagy can affect the metabolism of osteoblasts and osteoclasts, thus affecting bone homeostasis. Therefore, using autophagy as a theme, this review outlines the basic process of autophagy, the relationship between autophagy and osteoblasts and osteoclasts, and summarizes the latest research progress of common autophagic signaling pathways in osteoblasts and osteoclasts. The regulatory effects of protein molecules and natural compounds on the autophagy pathway of osteoblasts and osteoclasts discovered in current research are summarized and discussed. This will help to further clarify the mechanism of osteoporosis, understand the relationship between autophagy and osteoporosis, and propose new therapeutic strategies and new ideas for anti-osteoporosis.Keywords: osteoporosis, osteoblast, osteoclast, autophagy signaling pathway, natural compounds